The Hidden Work of Incidental Mentoring in the Hardest-to-Staff Schools - Jo Lampert; Amy McPherson; Alonso Casanueva Baptista; Amelia Hawkins (Education Sciences, 2025)
In a climate of pervasive teacher shortages, initiatives have focused on attracting new teachers to the profession, with hardest-to-staff schools more likely to fill vacancies with early-career teachers, including those with conditional status. In Australia, workforce policy prioritises induction and mentoring to support transition to the profession and improve retention. This paper aims to understand mentor teacher experiences in hardest-to-staff schools, where a growing cohort of inexperienced teachers increases the need for mentoring. The analysis is based on data from semi-structured interviews conducted with teachers in six schools across two Australian states, as part of a larger project exploring work experiences of teachers in hardest-to-staff schools. In addition to formal mentoring, our findings illustrate that in these schools, informal and incidental mentoring is widespread. Further, the iterative nature of novice teacher induction creates a sense of ambivalence in longer-serving teachers. While experienced teachers find reward in supporting early-career colleagues, the hidden labour inherent to constant incidental mentoring encroaches on the time available to manage their own workload, sometimes leading to frustration and even resentment. We conclude that while mentoring is crucial with so many new entrants to the profession, policymakers should be aware of the labour associated with increased incidental mentoring to avoid unintended consequences for teachers who find themselves in the position of supporting growing numbers of new staff.